ROLE ANALYSIS OF THE POWER OF REFERENCE GROUPS ON THE ONLINE REPURCHASE INTENTION - Ni Putu Cempaka Dharmadewi Atmaja; Ni Made Dwi Puspitawati (AIBPM Publisher, 2019)
The development of the internet has a significant impact on business development. Various convenience in conducting transactions has caused more online shops grow in Indonesia. As long as the rapid competition, business people in online stores expect customers to repurchase. Not only service quality and satisfaction are considered in the repurchase intention in the online store, but also it can pay attention to the power of the reference group as one of the considerations for consumers to repurchase. The purpose of this study was to determine the role of the power of reference groups variables in strengthening the relationship between the quality of e-commerce services and customer satisfaction with online repurchase intention. The sample in this study was a number of 100 respondents who were students in the city of Denpasar which were spread in several famous universities in Denpasar. The sampling technique uses purposive sampling. Methods of data collection using questionnaire techniques. Data were analyzed using multiple linear regression analysis and Test Moderated Regression Analysis (MRA). The results showed that the quality of e-commerce services and customer satisfaction had a positive and significant influence on the online repurchase intention. The power of the reference group is a moderator variable on the relationship between the quality of e-commerce services and customer satisfaction. The power of the reference group can strengthen the positive relationship between the quality of e-commerce services to online purchase intention, but the power of trust in the reference group does not strengthen the positive influence of satisfaction on the online repurchase intention.